Study the Behavior of Dual System (frames - shear walls) Using the Synthetic Time Histories Analysis - تريكية علي; نداف قصي; عيسى حسان (Latakia University Journal -Engineering Sciences Series, 2021)
Earthquakes in many parts of the world have revealed weaknesses in buildings in these countries. Where the experience gained from the observations and studies conducted on this subject led to increased knowledge about seismic evaluation. It is expected that the buildings will be deformed in a flexible way when exposed to severe earthquakes. Therefore, post- flexible behavior should be taken into account when assessing the seismic performance of buildings. Therefore, it is preferable to use nonlinear analysis procedures with the aim of evaluation, because behavior beyond flexibility cannot be determined directly through flexible analysis. The purpose of this study is to study the behavior of dual system (frames - shear walls) using the synthetic time histories analysis through study case , by conducting an applied analytical study on two constructs of dual systems, where time history were used for real earthquakes that were scaling by using the time domain and the frequency domain to suit the Syrian response spectrum. After finishing the analysis, we have discussed changing the displacements ,story drifts and stresses generated in the construction components.